A Study of Statics on Driyarkara Electric Automobile Chassis Prototype - Achilleus Hermawan Astyanto; Yana Resti Yanto; Adolf Baskoro Wisnu Adi (Universitas Sanata Dharma, 2020)
A design phase commonly initiates either a product invention or development. Before it continues to the fabrication steps, a modern computational, enabling a simulation study during the phase, often gives opportunity to develop its effectiveness and efficiency. Through several boundary conditions, some analytical and/or computational approaches could be determined. This paper aims to elaborate both static simulations and simple experimental tests on an electric automobile chassis prototype. An application based on finite element analysis was assessed to carry out both von Misses stresses and the nodal displacements regarding the construction and/or material strength to a static loads mode. Furthermore, an experimental based examination was also executed as a simple physical validation. The studies emphasize accepted results on von Misses stresses and nodal displacements for both simulation and experimental approaches.Keywords: Chassis Statics, von Misses stresses, nodal displacements, finite element